Identification of the pXO1 plasmid in attenuated Bacillus anthracis vaccine strains - Liang, Xudong (Virulence, 2016)
Anthrax toxins and capsule are the major virulence factors of Bacillus anthracis. They are encoded by genes located on the plasmids pXO1 and pXO2, respectively. The vaccine strain Pasteur II was produced from high temperature subcultures of B. anthracis, which resulted in virulence attenuation through the loss of the plasmid pXO1. However, it is unclear whether the high temperature culture completely abolishes the plasmid DNA or affects the replication of the plasmid pXO1. In this study, we tested 3 B. anthracis vaccine strains, including Pasteur II from France, Qiankefusiji II from Russia, and Rentian II from Japan, which were all generated from subcultures at high temperatures. Surprisingly, we detected the presence of pXO1 plasmid DNA using overlap PCR in all these vaccine strains. DNA sequencing analysis of overlap PCR products further confirmed the presence of pXO1. Moreover, the expression of the protective antigen (PA) encoded on pXO1 was determined by using SDS-PAGE and western blotting. In addition, we mimicked Pasteur's method and exposed the A16R vaccine strain, which lacks the pXO2 plasmid, to high temperature, and identified the pXO1 plasmid in the subcultures at high temperatures. This indicated that the high temperature treatment at 42.5°C was unable to eliminate pXO1 plasmid DNA from B. anthracis. Our results suggest that the attenuation of the Pasteur II vaccine strain is likely due to the impact of high temperature stress on plasmid replication, which in turn limits the copy number of pXO1. Our data provide new insights into the mechanisms of the remaining immunogenicity and toxicity of the vaccine strains.